Arbuscular mycorrhizal fungi communities and promoting the growth of alfalfa in saline ecosystems of northern China - Xu, Wen; Liu, Qianning; Wang, Baiji; Zhang, Na; Qiu, Rui; Yuan, Yuying; Yang, Mei; Wang, Fengdan; Mei, Linlin; Cui, Guowen (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) are universally distributed in soils, including saline soils, and can form mycorrhizal symbiosis with the vast majority of higher plants. This symbiosis can reduce soil salinity and influence plant growth and development by improving nutrient uptake, increasing plant antioxidant enzyme activity, and regulating hormone levels. In this study, rhizosphere soil from eight plants in the Songnen saline-alkaline grassland was used to isolate, characterize, and screen the indigenous advantageous AMF. The promoting effect of AMF on alfalfa (Medicago sativa L.) under salt treatment was also investigated. The findings showed that 40 species of AMF in 6 genera were identified by high-throughput sequencing.Glomus mosseae (G.m) and Glomus etunicatum (G.e) are the dominant species in saline ecosystems of northern China. Alfalfa inoculated with Glomus mosseae and Glomus etunicatum under different salt concentrations could be infested and form a symbiotic system. The mycorrhizal colonization rate and mycorrhizal dependence of G.m inoculation were significantly higher than those of G.e inoculation. With increasing salt concentration, inoculation increased alfalfa plant height, fresh weight, chlorophyll content, proline (Pro), soluble sugar (SS), soluble protein (SP), peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) activity, while decreasing malondialdehyde (MDA) content and superoxide anion production rate. The results highlight that inoculation with G.m and G.e effectively alleviated salinity stress, with G.m inoculation having a significant influence on salt resistance in alfalfa. AMF might play a key role in alfalfa growth and survival under harsh salt conditions.